INTEGRATING GAME-BASED WARM-UP AND DEEP LEARNING FOR MOTOR, COGNITIVE, AND CHARACTER DEVELOPMENT IN ELEMENTARY PHYSICAL EDUCATION - Jeffry Trinando; Ugi Nugraha; Alek Oktadinata (Universitas Islam Negeri Mataram, 2025)
Developing motor, cognitive, and character skills in elementary physical education remains a critical challenge, as conventional warm-up activities often emphasise physical readiness alone while neglecting deeper learning opportunities. Addressing this gap, the present study examines the effectiveness of a game-based warm-up model integrated with deep learning principles in fostering holistic student outcomes. This research employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group. The population consisted of Grade V elementary students in Batang Hari District, Jambi Province, from which 70 students were randomly selected and assigned into experimental (n = 35) and control (n = 35) groups. Instruments included a motor skills test, a 25-item cognitive test, and a 30-item character scale. Data were validated for reliability (Cronbach’s ? = 0.79–0.87) and analysed using normality, homogeneity, and hypothesis testing (independent samples t-test). Results revealed a significant improvement in the experimental group’s outcomes (M = 76.48) compared to the control group (M = 61.25), with t(68) = 10.245, p < 0.001. The effect size was huge (Cohen’s d = 3.70), and the normalised gain reached a moderate level (n-Gain = 0.48). These findings confirm that integrating game-based warm-up with deep learning enhances physical readiness and promotes higher-order thinking and value internalisation. The novelty of this study lies in positioning warm-up as a pedagogical platform that bridges motor competence, cognitive engagement, and character development. The implications extend to teachers, schools, and policymakers in advancing holistic physical education aligned with 21st-century educational goals.